Людські вади в поетичній інтерпретації Климентія Зиновієва - Циганенко, Вікторія Леонідівна; Tsyhanenko, Victoria (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті виявлені риси людського характеру, що мали негативне значення у творах Климентія Зиновієва. Проаналізовано вісім віршів, які належать перу зазначеного автора. У роботі було вивчено не тільки зміст творів, а й художні засоби, притаманні бароко, за допомогою яких Климентій Зиновіїв описує вади людського характеру. The traits of human character which the auteur considered to be negative were found out on the base Klimentii Zinoviiv epigram studies. Eight poems of the author was analyzes. The author considered negative traits of human nature is interference in other people's affairs, condemnation of others, appropriation of another's wealth, greed, stinginess, drowsiness, ignorance, envy. Each epigram ends with a teaching, a moral. In the article was study not only the content of poems, but also artistic means used by the author. Klimentii Zinoviiv used trops as epithets, comparisons, synonyms, antonyms, oppositions, phraseological turns, allocution etc. for the transmission of negative traits of human nature. These artistic devices are characteristic of the Baroque era. Analyzing the works, we can conclude that Klimentii Zinoviiv did not have a high artistic talent, but his work was of great importance in instructive, moral and religious plans.
The Negative Traits of Human Character in Poetic Interpretation of Klimentii Zinoviiv
Keywords: негативні людські вади; Климентій Зиновіїв; поетика; епіграми; бароко; negative human traits; Klimentii Zinoviiv; poetics; epigrams; baroque